Analysis of student errors in solving statistics questions visited from learning style - Nabilah, Naurah Nadiatun; Triyana , Illah Winiati (Universitas Mercu Buana Yogyakarta, 2023)
Accompanied by advances in modern data analysis technology, the abundance of social data in the industrial revolution 4.0 motivates educators to incorporate statistical principles into classroom learning. Questions covering statistical material are still difficult for students to solve, according to previous research. This research aims to determine the types of errors made by students in solving statistics problems based on learning styles (visual, auditory and kinesthetic). Ninth grade students at SMP Darussalam Tegal Joyo participated in this research, which used a qualitative descriptive methodology. The results of this research show that 1. visual learners make conceptual and procedural errors in this case they do not understand the concept of combined average, so the formula they use when solving problems is not precise and the way to calculate the median class does not use cumulative frequency. 2. Auditory learners make conceptual and procedural errors, they misunderstand the concept of compound average and also fail to use cumulative frequency to obtain median class. 3. Kinesthetic participants made a procedural error by not using cumulative frequency to get the median class.